1984
DOI: 10.1046/j.1467-6427.1984.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for clinicians considering family therapy research

Abstract: This paper is written by cliniciansfor clinicians who are thinking about or planning to evaluate family therapy.The basic premise is that to be successful a research project must be built from the beginning on a very solid foundation. This foundation is built from a careful consideration of various research problems which are interrelated yet which can be solved when addressed in a particular sequence. The paper describes eight stages which must be followed in any research project. The authors illustrate these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
2
3
0
Order By: Relevance
“…Similar findings had been reported using partially disguised illustrations of seven family patterns and two distractors by Fosson and Quan (1986). In that study, complete agreement (27.7%) and partial agreement (an additional 29.8%) were found between the consensual choice of nuclear family members and independently reached clinical formulations.…”
Section: Commentssupporting
confidence: 87%
See 1 more Smart Citation
“…Similar findings had been reported using partially disguised illustrations of seven family patterns and two distractors by Fosson and Quan (1986). In that study, complete agreement (27.7%) and partial agreement (an additional 29.8%) were found between the consensual choice of nuclear family members and independently reached clinical formulations.…”
Section: Commentssupporting
confidence: 87%
“…The educational effectiveness of the instructional package was documented by pre-test, post-test and a follow-up questionnaire (Fosson et al, 1982). The workshop participants showed significant improvement in identifying the organizational patterns of videotape presented families between the pre-test and post-test period.…”
Section: Development Of the Instrumentmentioning
confidence: 99%
“…During a period of repeat presentations of the workshops, it became clear that experienced physicians could identify families in their practices, with the illustrated family's organizational style (but were limited by their terminology) by examining the visual material for a couple of minutes without any explanation or discussion. This experience was similar to that reported with family therpists (Campbell and de Carteret, 1984). It emphasized the effectiveness and efficiency of visual communication and stimulated speculation about the ubiquity and accessibility of this body of knowledge.…”
Section: Instrument Developmentsupporting
confidence: 79%
“…Another important clinical finding was that feedback from clients in ethnographic interviews was used by therapists to change tactics or make adjustments prior to termination. As noted earlier, therapists have repeatedly lamented that traditional research has had little direct relevance to their particular case(s) and that any meaningful information is reported after the completion of treatment (Campbell & de Carteret, 1984;Liddle, 1991a;Schwartz & Breunlin, 1983;Wynne, 1983). However, therapists in this study overwhelmingly reported that these research methods were invaluable because findings could be used in providing better treatment.…”
Section: Discussionmentioning
confidence: 75%